2011
DOI: 10.1080/1369183x.2011.572486
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Migration and Changing Nationalisms: The Vietnamese Return Diaspora and Reconstruction of Vietnamese Nationhood

Abstract: The Vietnamese diasporic population, largely constituted within international and regional political turbulences in the 1970s and early 1980s, has been swiftly recycled over the last decade. Many first-and second-generation overseas Vietnamese have been returning to Vietnam to live and work. This article examines the interactive dynamics between the homeland society and the returning migrants, and the impact of return migration on Vietnamese nationhood. Unlike most transnational studies that centre on the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…In Rachel's case 'passing' as a local Vietnamese is seen as a verification of her ethnic authenticity. In contrast, other research has shown how the Viet Kieu returnees are often easily identifiable by the local population (Chan and Tran 2011;Carruthers 2002), because they are seen as 'fatter' (Carruthers 2002), and also fairer skinned.…”
Section: British-born Vietnamese Women's Narratives Of Visits To Vietnammentioning
confidence: 86%
See 2 more Smart Citations
“…In Rachel's case 'passing' as a local Vietnamese is seen as a verification of her ethnic authenticity. In contrast, other research has shown how the Viet Kieu returnees are often easily identifiable by the local population (Chan and Tran 2011;Carruthers 2002), because they are seen as 'fatter' (Carruthers 2002), and also fairer skinned.…”
Section: British-born Vietnamese Women's Narratives Of Visits To Vietnammentioning
confidence: 86%
“…Focusing on the second-generation, Espiritu and Tran (2002) show how 'symbolic transnationalism' takes place among young Vietnamese Americans who engage symbolically with the homeland through the transnational flow of ideas, norms and values and also 'imagined returns to the homeland through selective memory, cultural rediscovery and sentimental longings '(2002; 369). Return migration to Vietnam from the international diaspora has been an increasing trend in recent years (Carruthers 2002, Chan and Tran 2011, Chan 2013, Thai 2011, 2014. Over the last two decades the relaxation of Vietnamese Government Policy towards the Viet Kieu (Overseas Vietnamese) on visa requirements to enter the country, their ability to invest in business and send money to Vietnam, and travel between provinces once in Vietnam, has contributed to this increasing return migration (Phuong 2000, Chan 2011and Pham 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overwhelmingly, research in migration studies about diasporic visits (also called 'visiting friends and relatives' or VFR) focuses on symbolic and ideological identities related to belonging in the nation or family (Chan and Tran 2011;Heine, Licata, and Azzi 2007;Potter and Phillips 2006;Reynolds 2006). Buried within these discussions are a persistent problematic of class distinction, obscured by the focus on the ethno-national and often implicit in the fact of migration, whereby visiting relatives or co-nationals become other -sometimes not unlike tourists -through their relatively increased access to capital (Marlière 2006;Stephenson 2002).…”
Section: Diasporic Mobility: Visiting a Moroccan 'Home'mentioning
confidence: 99%
“…In the age of growing “brain circulation,” how to gain “brain” from the diaspora, therefore, has become a critical policy issue for many countries (Finch et al., ; Chan and Tran, ). States increasingly try to tap into diaspora resources by extending the boundary of citizenship to emigrants and their descendants (Bauböck, ; Brubaker, ).…”
Section: Introductionmentioning
confidence: 99%